Insights into the pathogenesis of vein graft disease: lessons from intravascular ultrasound - Angelini Gianni D; Murphy Gavin J (Cardiovascular Ultrasound, 2004)
Abstract The success of coronary artery bypass grafting (CABG) is limited by poor long-term graft patency. Saphenous vein is used in the vast majority of CABG operations, although 15% are occluded at one year with as many as 50% occluded at 10 years due to progressive graft atherosclerosis. Intravascular ultrasound (IVUS) has greatly increased our understanding of this process. IVUS studies have shown that early wall thickening and adaptive remodeling of vein grafts occurs within the first few weeks post implantation, with these changes stabilising in angiographically normal vein grafts after six months. Early changes predispose to later atherosclerosis with occlusive plaque detectable in vein grafts within the first year. Both expansive and constrictive remodelling is present in diseased vein grafts, where the latter contributes significantly to occlusive disease. These findings correlate closely with experimental and clinicopathological studies and help define the windows for prevention, intervention or plaque stabilisation strategies. IVUS is also the natural tool for evaluating the effectiveness of pharmacological and other treatments that may prevent or slow the progression of vein graft disease in clinical trials.